2014
DOI: 10.1016/j.worlddev.2014.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Process of Agricultural Technology Adoption: Mineral Fertilizer in Eastern DR Congo

Abstract: While there is a large literature on agricultural technology adoption, evidence from the poorest countries is still lacking and the decision-making process of farmers is still poorly understood. We empirically analyze mineral fertilizer adoption among poor and food insecure smallholder farmers in South-Kivu, eastern DR Congo, after its introduction by a research and extension program. We disentangle the adoption process in an awareness step, a tryout decision, and a continued adoption decision. We show that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
141
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 49 publications
(54 reference statements)
20
141
0
4
Order By: Relevance
“…Here in particular the stabilization of the nutrients in the soil, closing the nutrient cycles, or a more efficient use of the fertilizer nutrients are discussed (e.g., [9,88]). Other publications have the use of mineral fertilizer in developing countries in focus (e.g., [89,90]). Furthermore, tools for diagnosis to enable a better estimation of the crop nutrient status are evaluated by a number of publications (e.g., [91,92]).…”
Section: Different Eco-innovations In the Fertilizer Sectormentioning
confidence: 99%
See 3 more Smart Citations
“…Here in particular the stabilization of the nutrients in the soil, closing the nutrient cycles, or a more efficient use of the fertilizer nutrients are discussed (e.g., [9,88]). Other publications have the use of mineral fertilizer in developing countries in focus (e.g., [89,90]). Furthermore, tools for diagnosis to enable a better estimation of the crop nutrient status are evaluated by a number of publications (e.g., [91,92]).…”
Section: Different Eco-innovations In the Fertilizer Sectormentioning
confidence: 99%
“…That goes in line with the quality of support. Here a good support or consulting could stimulate the farmers to try a new product [9,88,89,133]. New products are in need for a purchase opportunity by farmers.…”
Section: Drivers For Continuous Product Innovations (Goods)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, studies found that land expansion seems impossible since the population keeps on increasing and subsequently, the per-capita land is already at its minimal making it impossible to expand the area under cultivation (Asfaw et al, 2012;de Janvry et al, 2003;Islam, 1995). The second option of increasing productivity through technology innovation and application also requires complementation since it faces several constraints like, technology adoption is time consuming, requires high level of technical knowledge to implement, can be risky, costly and inaccessible, which hinders technology adoption (Abateet al, 2016;Brick and Visser, 2015;Lambrecht et al, 2014;Parks et al, 2015). Therefore, the promising solution to increase food production mainly lies in increasing land productivity by improving resource use efficiency (Islam, 1995;Rahman, 2003).…”
Section: Introductionmentioning
confidence: 99%